PENGARUH PEMBERIAN REBUSAN DAUN SIRIH HIJAU TERHADAP KEJADIAN KEPUTIHAN PADA REMAJA PUTRI SMA MUHAMMADIYAH RAMBAH - Wahyuny, Romy; Andini, Dwi Putri; Andriana, Andriana; Fitria, Rahmi (Ensiklopedia of Journal, 2025)
Adolescents often experience vaginal discharge, to overcome it, they can use non-pharmacological treatment, one of which is green betel leaves. Green betel leaves have health benefits. Where one of the benefits is for vaginal discharge and to maintain vaginal cleanliness. Betel leaves contain a chemical compound called eugenl. This antifungal compound can kill the fungus candida albicans, known as one of the causes of vaginal discharge. This study aims to determine the effect of giving green betel leaf decoction on the incidence of vaginal discharge in adolescent girls at Muhammadiyah Rambah High School. The research method uses the Pre-Experimental method with a one-group pretest-posttest design approach. The instruments used in this study were questionnaires and observation sheets. The sampling technique in this study is a saturated sampling technique where all populations in this study are sampled, namely 20 respondents. The method of giving betel leaf therapy is given for 6 days, 2 times a day as much as 200 cc. The results of this study found that there was an effect of green betel leaves of 0.000 <0.05 so that it can be said that there is an effect of giving green betel leaf decoction on the incidence of vaginal discharge. It is hope d that young women who experience vaginal discharge can use boiled water with green betel leaves to reduce the occurrence of vaginal discharge.Bibliography : 32 (2016-2024)Keywords : Green Betel Leaf, Whitish, Juvenile, Candida Albicans Fungus